Avoidant Attachment, Withdrawal-Aggression Conflict Pattern, and Relationship Satisfaction: A Mediational Dyadic Model - Bretaña, Ione; Alonso-Arbiol, Itziar; Recio, Patricia; Molero, Fernando (Frontiers in Psychology, 2022)
This study was conducted with the purpose of analyzing the combined and mediating effect of actor’s withdrawal — partner’s demand conflict resolution strategies between avoidance attachment dimension and relationship satisfaction. We conducted a dyadic study with 175 heterosexual couples (aged between 18 and 72 years) filled in the questionnaires. Six hypotheses were tested using the Actor-Partner Interdependence Model with mediation analysis (APIMeM). Results showed that the avoidance dimension of attachment was more strongly associated with actor’s withdrawal strategy than with demand/aggression strategy. Furthermore, avoidance attachment was negatively associated with both actor’s and partner’s relationship satisfaction, being higher the actor effect. Withdrawal strategy was a mediator between actor’s avoidance and actor’s relationship satisfaction, but it was not a mediator for partner’s relationship satisfaction. The interactive pattern of actor’s withdrawal – partner’s demand/aggression was associated with low levels of both actor’s and partner’s relationship satisfaction. These results point out to the need of discerning the interactive pattern of conflict solving strategies as well as their intertwined effect on relationship satisfaction.